Constraining context: Situating datafication in public administration - Reutter, Lisa (New media & society, 2022)
The imaginary of data-driven public administration promises a more effective and knowing public sector. At the same time, corporate practices of datafication are often hidden behind closed doors. Critical algorithm studies, therefore, struggle to access and explore these practices, to produce situated accounts of datafication and possible entry points to reconfigure the emerging data-driven society. This article offers a unique empirical account of the inner workings of data-driven public administration, asking the overall question of how sociotechnical imaginaries of datafication are constrained in the context of public administration. Teams working on datafication in two Norwegian public sector entities have been followed and interviewed over the course of 2 years (2018–2020). While sociotechnical imaginaries thrive in organizational culture and policy discourse alike, the observed data teams struggle to realize data assemblages due to a variety of structural and institutional constraints.